Durability, life cycle cost and life cycle assessment of binary mixtures with fly ash, rice husk ash and concrete demolition waste - Lima, Cristian Jonathan Franco de; Ribeiro, Francisco Roger Carneiro; Modolo, Regina Célia Espinosa; Isaia, Geraldo Cechella; Mancio, Mauricio (Ambiente Construído, 2021)
This study analyses, by means of lifespan cost and lifespan assessment, the production of binary concrete admixtures compound by artificial pozzolan and concrete demolition waste. Ten formulations were developed, differentiating them in terms of mixtures, binder and aggregate content, in order to verify their potential use in concrete columns. The replacements were 25% of Portland cement for fly ash and rice husk ash, 15% and 30% of natural coarse aggregates for concrete demolition waste. The results revealed that the mixtures with pozzolan and demolition waste showed higher resistance to chloride penetration. The lowest concrete cost was achieved in the highest compressive strength (35 MPa) and the concrete admixture containing 15% replacement of the natural coarse aggregate by the recycled concrete aggregate and 25% substitution of cement by rice husk ash can be classified as the most environmentally sustainable one, especially in carbon dioxide emissions, among the mixtures studied.